Development of the hybrid adaptive method for noise reduction in the bitmap image of the part drawing - Молчанова, Вера Сергеевна (Eastern-European Journal of Enterprise Technologies, 2015)
An original hybrid method FILTRATOR that allows to eliminate the noise in monochrome and binary bitmap images of the part drawings was proposed. The analysis of the characteristics of the scanned images of the part drawings and characteristic noise, not allowing to get a satisfactory result by standard noise reduction methods was performed. The main features of bitmap images of drawings are the presence of fine lines, filtering of which by standard methods leads to disruption of the integrity and coherence of the part contours, as well as specific types of noise and distortion. The peculiarity of the proposed hybrid method is its phased implementation. At the first stage, monochrome noise is eliminated by the automatic tone adjustment of the monochrome bitmap image of the part drawing based on the analysis of its brightness and contrast histograms. At the second stage, the remaining binary noise is eliminated by adaptive method, which involves selecting an effective combination of filtering methods: the contour mask method, modified aperture method kFill, median, morphological and logical filtering methods, as well as selecting structural elements based on the block-by-block evaluation of the image parameters: contour line thickness, noise type and level. The proposed hybrid method FILTRATOR effectively eliminates noise in binary bitmap images of the part drawings, while maintaining the integrity and continuity of contours. The comparative qualitative and quantitative testing results of the FILTRATOR method and spatial, frequency, and morphological filtering methods were given. The comparison was performed using the MSE, PSNR and UQI criteria. The result of the comparison showed the superiority of the FILTRATOR method in terms of filtering quality of artifacts in scanned bitmap images of the part drawings.